Determinants of primary school access and participation rates in the pastoralist Turkana County, Kenya - Migosi, Joash; Nanok, Daniel; Ombuki, Charles; Ombuki, Kennedy N.; Evusa, Zablon; Metet, Joseph (© 2013 Academic Journals, 2012)
The status of education in Turkana County is typical of all the ASAL counties of Kenya characterised by low enrolments levels, high dropout rates and poor infrastructural development. This study was undertaken to determine factors that could enhance pupils’ access and participation in primary school education in Kakuma and Lokichoggio divisions of Turkana County in north western Kenya. The purpose of the study was to find out the factors that enhance pupils’ access and participation in primary school education in Turkana County, using Kakuma and Lokichogio divisions. The two divisions’ nine schools were randomly selected to form the sample population for the study. The research study employed the descriptive survey design. The data collection instruments utilized included questionnaires administered to head teachers and teachers, focus group discussions conducted for pupils and parents and interview guides used for the key informants and head teachers. The data collected was analysed using descriptive statistics. Qualitative data was analysed and presented as respondents’ opinions on the status of education access and participation in the area of study. The study revealed that provision of security, establishment of boarding schools, adequate provision of food to schools, good school infrastructural development, availability of teachers and learning materials were the strongest factors that enhance access and participation in primary school education in the area of study. This study recommends that more boarding schools be established in Turkana County. Adequate supply of food to all schools and creation of feeder schools in the very interior nomadic pastoralist areas will enhance access and participation to education. Enough teachers should also be posted to the area. Key words: Determinants, Primary school, access rates, participation rates, pastoralist, Turkana County, Kenya